Molecular Techniques in the Microbial Ecology of Fermented Foods - Cocolin, Luca.; Ercolini, Danilo; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Thanks to the application of methods allowing precise imaging of microbial ecology, the field of food fermentation has experienced exponential growth in the last few years. This has resulted in the availability of new information on the structure and dynamics of the microbial populations during fermented food production. Molecular Methods and Microbial Ecology of Fermented Foods presents the latest findings in microbial ecology as determined by the application of molecular methods, reports the most recent advances in the field, and offers details on primers and protocols most suitable for studying specific food ecosystems. It provides analytical details and suggestions useful in research, as well as evaluation of the criticism of using novel approaches in food fermentation microbiology. This book also discusses new insights drawn from the use of bio-molecular techniques in the microbial ecology of fermented foods. About the Authors: Luca Cocolin is an associate professor at the University of Turin, Italy. Danilo Ercolini is a researcher at University of Naples Federico II, Naples, Italy.
Molecular Techniques in Food Fermentation: Principles and Applications -- Dairy Products -- Fermented Meat Products -- Sourdough Fermentations -- Vegetable Fermentations -- Wine Fermentation -- Beer Production -- Other Fermentations -- Probiotics: Lessons Learned from Nucleic Acid-based Analysis of Bowel Communities -- Bioinformatics for DNA Sequence-based Microbiota Analyses -- Role of Bacterial ‘Omics’ in Food Fermentation.
Keywords: Industrial engineering; Production engineering; Biotechnology; Microbiology; Food—Biotechnology.; Industrial and Production Engineering; Biotechnology; Microbiology; Food Science